Epidemiology of Plasma Cell Leukemia in the Czech Republic - Zapletalova, M; Krejci, D; Jarkovský, J; Muzik, J; Dusek, L; Pour, L (Klinicka onkologie, 2019)
BACKGROUND: Plasma cell leukemia (PCL) is a rare but most aggressive form of monoclonal gammopathies. PCL is characterized by the presence of clonal plasma cells in peripheral blood. There are two forms of PCL - primary which presents de novo in patients with no evidence of previous multiple myeloma and secondary which is a leukemic transformation of relapsed or refractory dis-ease in patients with previously recognized multiple myeloma. MATERIALS AND METHODS: This is the first study to provide information on PCL epidemiology in the Czech population us-ing The Czech National Cancer Registry (CNCR) as the basic source of data for the population-based evaluation of PCL epidemiology. RESULTS: Accord-ing to CNCR data, there were on average six newly dia-gnosed cases of PCL and four deaths caused by PCL each year in the Czech Republic in the period 2000- 2015. PCL incidence in the Czech Republic was reported at 0.57 per million in 2000- 2015. We suppose that most reported cases of PCL are primary PCL because secondary PCL is a relapse of a previously reported myeloma and, in most cases, is not coded as an independent dia-gnosis in the CNCR. CONCLUSION: Data from registries such as the CNCR can provide useful information on epidemiology of various dis-eases. These data, however, have several limitations, such as dia-gnostic criteria and proper cod-ing of not only the dis-ease itself, but also its various forms. These limitations have to be taken into account dur-ing the process of results interpretation. Key words plasma cell leukemia -  epidemiology -  Czech National Cancer Registry (CNCR) -  Czech Republic.
Keywords: senioři; senioři nad 80 let; plasma cell leukemia - epidemiology - Czech National Cancer Registry (CNCR) - Czech Republic; kojenec; Incidence; mladiství; Česká republika; Middle Aged; mužské pohlaví; Infant; incidence; Adult; mladý dospělý; Czech Republic; dítě; Child; plazmocelulární leukemie; Aged, 80 and over; Child, Preschool; Infant, Newborn; Leukemia, Plasma Cell; Young Adult; ženské pohlaví; novorozenec; Humans; předškolní dítě; lidé středního věku; dospělí; Female; Aged; Adolescent; lidé; Male